Strategi Komunikasi Interaktif Melalui Instagram Supplier Merpati dalam Menumbuhkan Citra Produk Roda Pagar - Abdul Mubarok; Murtiadi; Roynaldi Arista (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This research aims to analyze the interactive communication strategy implemented by Suplier Merpati Indah through the Instagram platform in fostering a positive customer image towards its Roda Pagar products. The background of this study is driven by the development of social media as a strategic tool for building emotional relationships and customer loyalty. This study employs a qualitative research method, utilizing in- depth interviews, participatory observation, and documentation as data collection techniques. The results indicate that Merpati Indah consistently applies communication strategies focusing on strong visual branding, active two-way interactions, and the presentation of educational and narrative content through storytelling. Instagram features such as posts, stories, and direct messages are optimally utilized to build engagement and customer trust. Visual consistency in the feed, prompt responses to inquiries, and a human-centered approach in digital interactions are key factors in creating positive perceptions and customer loyalty. The study concludes that interactive communication strategies through Instagram, when strategically designed, play a crucial role not only in increasing brand awareness but also in shaping a positive brand image and strengthening emotional bonds with customers. These findings are expected to serve as a practical reference for business practitioners in developing effective digital communication strategies in the era of social media.